2012
DOI: 10.1212/wnl.0b013e3182535cf6
|View full text |Cite
|
Sign up to set email alerts
|

Survival in MS

Abstract: Objective: To examine the effects of interferon beta (IFN␤)-1b on all-cause mortality over 21 years in the cohort of 372 patients who participated in the pivotal randomized clinical trial (RCT), retaining (in the analysis) the original randomized treatment-assignments. Methods:For this randomized long-term cohort study, the primary outcome, defined before data collection, was the comparison of all-cause mortality between the IFN␤-1b 250 g and placebo groups from the time of randomization through the entire 21-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
81
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(84 citation statements)
references
References 33 publications
3
81
0
Order By: Relevance
“…However, the diagnosing of more benign cases had probably a limited impact on prevalence, leaving increased survival as the most likely explanation to our findings. Improved survival in MS, possible due to more frequent use of advanced disease-modifying therapies, 31 was probably the most important factor related to the observed increase in prevalence. The importance of improved survival on the observed increase in prevalence was also supported by the shift towards an older age distribution of the present 2013 prevalence cohort compared with the prevalence reported in the 2003 study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the diagnosing of more benign cases had probably a limited impact on prevalence, leaving increased survival as the most likely explanation to our findings. Improved survival in MS, possible due to more frequent use of advanced disease-modifying therapies, 31 was probably the most important factor related to the observed increase in prevalence. The importance of improved survival on the observed increase in prevalence was also supported by the shift towards an older age distribution of the present 2013 prevalence cohort compared with the prevalence reported in the 2003 study.…”
Section: Discussionmentioning
confidence: 99%
“…The sample comprised of 202(31.9%) male, and 431(68.1%) females. (20)(21)(22)(23)(24), While (34.1%) of the respondents Aged between (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35), While (18.8%) of the respondents Aged more than 35. Table (3) that (34.4%) of the respondents belong to the eastern region, while (33.5%) of them belong to the western region, (20.4%) of them belong to the Central Region, and (7.3%) of them belong to the southern district.…”
Section: Methodology:-mentioning
confidence: 96%
“…Thirdly, general improvement in health care services and awareness of the condition may be increasing case ascertainment. Finally, increasing long-term survival may be due to improved general medical care and the possible beneficial effect of disease-modifying treatments [30]. That the latitudinal gradient in the prevalence of MS has remained constant over time suggests that factors other those accounting for the gradient per se may be responsible for the overall increase in prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has shown that early treatment with disease‐modifying therapy (in this case with IFN β ‐1b) was associated with a significant survival advantage over placebo in patients with MS followed up for 21 years 32. This decreasing mortality trend and the lack of a curative therapy means that patients and their caregivers are living with the consequences of MS for longer, and the associated morbidity can be significant.…”
Section: Discussionmentioning
confidence: 99%